Granisetron compared with prednisolone plus metopimazine as anti-emetic prophylaxis during multiple cycles of moderately emetogenic chemotherapy - Sigsgaard, T (Nature Publishing Group, 1999)
This randomized, double-blind, double-dummy parallel study compared the anti-emetic efficacy and tolerability of the serotonin antagonist granisetron with prednisolone plus the dopamine D(2) antagonist metopimazine during nine cycles of moderately emetogenic chemotherapy. Chemotherapy naive women with stage I or II breast cancer scheduled to intravenous cyclophosphamide, fluorouracil and methotrexate or cyclophosphamide, epirubicin and fluorouracil every 3 weeks were included. Patients received a single intravenous dose of granisetron 3 mg or a 3-day oral treatment with prednisolone 25 mg once a day plus metopimazine 30 mg four times a day. A total of 223 women were enrolled and 218 patients (97.8%) were evaluable for efficacy. Granisetron (n = 109) was superior to prednisolone plus metopimazine (n = 109) in the prophylaxis of acute nausea and vomiting during the first cycle of chemotherapy (P < 0.001) and prednisolone plus metopimazine was superior on days 2–5 (P = 0.002). Overall, granisetron was superior on days 1–5 (P = 0.009). The median number of cycles completed with granisetron was five (95% confidence interval 4–6) compared with two (95% confidence interval 2–2) for prednisolone plus metopimazine (P = 0.0019). Constipation and rash were reported more frequently with granisetron (P < 0.001 and P = 0.043 respectively) and palpitations more frequently with prednisolone plus metopimazine (P = 0.015). In conclusion, the number of cycles completed with granisetron was significantly higher than the number completed with prednisolone plus metopimazine, but the anti-emetic efficacy of both treatments declined during multiple cycles of moderately emetogenic chemotherapy. © 1999 Cancer Research Campaign